High-Resolution Simultaneous Multi-Slice Accelerated Turbo Spin-Echo Musculoskeletal Imaging: A Head-to-Head Comparison With Routine Turbo Spin-Echo Imaging - Gao, Feifei; Wen, Zejun; Dou, Shewei; Kan, Xiaojing; Wei, Shufang; Ge, Yinghui (Frontiers in Physiology, 2021)
imaging; however, its acquisition speed is limited and can be easily affected by motion artifacts. We aimed to evaluate whether the use of a simultaneous multi-slice TSE (SMS-TSE) sequence can accelerate MSK imaging while maintaining image quality when compared with the routine TSE sequence. Methods: We prospectively enrolled 71 patients (mean age, 37.43±12.56 [range, 20–67] years), including 37 men and 34 women, to undergo TSE and SMS sequences. The total scanning times for the wrist, ankle and knee joint with routine sequence were 14.92 min, 13.97 min and 13.48 min, respectively. For the SMS-TSE sequence, they were 7.52 min, 7.20 min and 6.87 min. Quantitative parameters, including the signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR), were measured. Three experienced MSK imaging radiologists qualitatively evaluated the image quality of bone texture, cartilage, tendons, ligament, meniscus, and artifact using a 5-point evaluation system, and the diagnostic performance of the SMS-TSE sequences was evaluated. Results: Compared with the routine TSE sequences, the scanning time was lower by 49.60%, 48.46%, and 49.04% using SMS-TSE sequences for the wrist, ankle, and knee joints, respectively. For the SNR comparison, the SMS-TSE sequences were significantly higher than the routine TSE sequence for wrist (except for Axial-T2WI-FS), ankle, and knee joint MR imaging (all p<0.05), but no statistical significance was obtained for the CNR measurement (all p>0.05). For the wrist joint, the diagnostic sensitivity, specificity, and accuracy were 88.24%, 100% and 92%. For the ankle joint, they were 100%, 75%, and 93.33%. For the knee joint, they were 7.50%, 85.71%, and 87.10%. Conclusions: The use of the SMS-TSE sequence in the wrist, ankle, and knee joints can significantly reduce the scanning time and show similar image quality when compared with the routine TSE sequence.